Effect of chain stiffness on the morphology of polyelectrolyte complexes. A Monte Carlo simulation study - Narambuena, Claudio Fabian (2010)
We have employed Monte Carlo simulations and a coarse grain model in order to analyze the final structure and morphology of complexes arising from the interaction between fully-flexible polycations and polyanions with different chain stiffness. Different morphologies, like globules, toroids and rods, are obtained depending on chain stiffness. It was observed that longer chains yield more frequently toroids than rods, as compared with shorter chains. However, the size of toroids does not depend entirely on the chain length. This suggests that the final structure of the toroids is highly dependent on the intrinsic rigidity of chain rather than on the electrostatic contributions. © 2010 Elsevier Ltd.